2018
DOI: 10.1111/boc.201700060
|View full text |Cite
|
Sign up to set email alerts
|

Integrin diversity brings specificity in mechanotransduction

Abstract: Cells sense and respond to the biochemical and physical properties of the extracellular matrix (ECM) through adhesive structures that bridge the cell cytoskeleton and the surrounding environment. Integrin-mediated adhesions interact with specific ECM proteins and sense the rigidity of the substrate to trigger signalling pathways that, in turn, regulate cellular processes such as adhesion, motility, proliferation and differentiation. This process, called mechanotransduction, influenced by the involvement of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 136 publications
(178 reference statements)
1
95
0
Order By: Relevance
“…We therefore suggest that this behavior may originate from the integrins that are involved in cell adhesion. Integrins subtypes have been shown to differently contribute to rigidity probing (60). For instance traction forces transmitted by α 6 β 1 integrins which are involved in cell adhesion on LN (61) were shown to be of smaller amplitude than those transmitted by the α 5 β 1 integrins on FN (62).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore suggest that this behavior may originate from the integrins that are involved in cell adhesion. Integrins subtypes have been shown to differently contribute to rigidity probing (60). For instance traction forces transmitted by α 6 β 1 integrins which are involved in cell adhesion on LN (61) were shown to be of smaller amplitude than those transmitted by the α 5 β 1 integrins on FN (62).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, multiple protein complexes that appear to be cell type specific and may associate with FAs dependent on distinct integrin subtypes (Seetharaman and Etienne-Manneville, 2018), are not only involved in recruiting microtubules to the vicinity of FAs, but also in keeping them anchored at these sites by preventing their depolymerisation or removal by the actin retrograde flow. In turn, FA-associated microtubules can also contribute to intracellular transport and signalling to alter FA dynamics as discussed below.…”
Section: Recruitment Of Cortical Partners Near Fasmentioning
confidence: 99%
“…α 6 β 4 integrins form the core of hemidesmosomes, which mainly connect to the intermediate filament network (Walko et al, 2015), although some recent reports have suggested that microtubules can also be associated with hemidesmosomes (Quintin et al, 2016). In contrast to hemidesmosomes, FAs and podosomes vary in their integrin composition and are mainly associated with the actin cytoskeleton (Seetharaman and Etienne-Manneville, 2018). FAs and the smaller focal complexes are adhesive structures that are essential for cell spreading and cell motility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A central element to mechanobiology is the understanding of how cells probe their extracellular environment (neighbouring cells and the ECM components) and exert or feel forces to mediate different cellular responses via adhesive proteins such as integrins, cadherins, and other mechanosensitive receptors [Sluysmans et al., ; Seetharaman and Etienne‐Manneville, ]. However, we want to specify here that the purpose of this editorial is not to describe the signalling processes induced by mechanical stresses, but to focus on how cells experience forces.…”
mentioning
confidence: 99%